The Effect of Job Satisfaction, Job Rotation, and Work Motivation on Employee Performance at PT. Bank Gunung Sewu Jakarta Branch - Yuni Susriati (Priviet Social Sciences Journal, 2023)
One of the important issues faced by the company's leaders is how to increase the productivity of its employees with good performance so that the company can achieve the goals to be achieved. Employee performance plays a very important, because the reciprocation of a company is highly dependent on whether or not the optimal performance of employees. To improve the performance of its employees, a company must first overcome the problems encountered, such as eliminating boredom, puts employees at the most appropriate position, and provide support to employees who experience a decrease in performance.This study aimed to analyze the influence of job satisfaction, the rotational position and work motivation, either partially or simultaneously, against the performance of employees of PT. Gunung Sewu Bank Jakarta Branch. This study uses a quantitative approach and techniques of data collection is done through a questionnaire distributed to 44 respondents who are all employees of PT. Gunung Sewu Bank Jakarta Branch. The sampling technique used is total sampling. The analysis used in this study is simple and multiple linear regression, simple and multiple correlation, coefficient of determination and t test and F test Research shows that job satisfaction has a positive and significant influence amounted to 74.9%, the rotational position has a positive effect of 71.5% and a positive effect on work motivation and a significant 74.3%. Similarly together, these three independent variables are positive and significant influence amounted to 80.0%. Results of this study prove that hypothesis Ha accepted and proven linear.